A Comparison of Computed Tomographic, Radiographic, Gross and Histological, Dental, and Alveolar Findings in 30 Abnormal Cheek Teeth from Equine Cadavers - Liuti, Tiziana; Smith, Sionagh; Dixon, Padraic M. (Frontiers in Veterinary Science, 2018)
Background: Equine cheek teeth disorders, especially pulpar/apical infections, can have very serious consequences due to the frequent extension of infection to the supporting bones and/or adjacent paranasal sinuses. Limited studies have assessed the accuracy of computed tomographic (CT) imaging in the diagnosis of these disorders and no study has directly compared imaging and pathological findings of the alveoli of diseased equine cheek teeth. Objective: To validate the accuracy of CT and radiographic imaging of cheek teeth disorders by comparing CT and radiographic imaging, gross and histological findings in abnormal cheek teeth and their alveoli extracted from equine cadaver heads. Study Design: Ex-vivo original study Methods: Fifty-four cadaver heads from horses with unknown histories that had died or been euthanized on humane grounds obtained from a rendering plant had radiography, CT imaging, and gross pathological examinations performed. Based on imaging and gross examination findings, 30 abnormal cheek teeth (26 maxillary and 4 mandibular) identified in 26 heads were extracted along with their dental alveoli where possible, and further CT imaging, gross and histological examinations were performed. Eight maxillary cheek teeth (including four with attached alveolar bone) from these heads, that were normal on gross and CT examinations, were used as controls. Results: Gross pathological and histological examinations indicated that 28/30 teeth, including two supernumerary teeth, had pulpar/apical infection, including pulpar and apical changes. A further supernumerary and a dysplastic tooth were also identified. Abnormal calcified tissue architecture was present in all three supernumerary and in the dysplastic tooth. CT imaging strongly indicated the presence of pulpar/apical infection in 27 of the 28 (96.4%) pulpar/apically infected teeth, including the presence of intra-pulpar gas (N=19/28), apical clubbing (N=20), periapical halo (N=4), root lysis or fragmentation (N=7), periapical gas (N=2). Also present were alveolar bone sclerosis (N=20), alveolar bone thickening (N=3) and lytic/erosive changes (N=8). Radiographic abnormalities strongly indicative of pulpar/apical infection including periapical sclerosis (N=8/28) and apical clubbing (N=14/28) were found in 14/28 (50%) of apically infected teeth. Histological changes were present in alveolar bone of all 21 cases of apical infection where alveolus remained attached to the tooth, and was marked in